Dublin Core for Recording Metadata of Experiments in Software Engineering: A Survey - Santana, Filipe A.; Cordeiro, André F. R.; OliveiraJr, Edson (Anais da Escola Regional de Engenharia de Software (ERES); 2023: Anais da VII Escola Regional de Engenharia de SoftwareDO - 10.5753/eres.2023.237790, 2023)
Metadata is defined as data about data. Metadata Standards represent structures for recording in order to promote data interoperability. This study focuses on investigating the Utility and Feasibility of the Dublin Core Standard for recording metadata associated with Software Engineering Experiments. A Survey was conducted with professionals and researchers who have experience. Eleven answers were collected. The observed results suggest positive research prospects.